(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Žižek’s Violence explores the global representation of violence. He distinguishes subjective and objective violence. Subjective violence is committed by a known actor. There is no obvious objective violence perpetrator. Žižek differentiates between symbolic (language-based) and systemic (systemic, sustained by capitalism, political, and economic structures) violence. This paper focuses on the application of Žižek’s theory of symbolic and systemic violence to the text of Anna Burns’ novel, Milkman.